Determination with a Genetic Algorithm of Reactant Coverages on H2/H2O Electrodes Based on Electrochemical Kinetics Under Reversible SOFC/EC Operation. Issue 6 (17th December 2020) - Koga, Y.; Hasegawa, K.; Lee, H.; Kameda, K.; Iida, Y.; Ihara, M.
Abstract: A scheme to quantify surface coverages of reactants at triple phase boundary (TPB) by electrochemical measurements was constructed to evaluate the electrode performance of solid oxide fuel cells and electrolysis cells (SOFC/EC). The developments of electrode requires that the intrinsic properties of materials separated from the effect of geometric structure of the electrode. The proposed reaction model at TPB of H2 /H2 O electrodes is composed of competitive adsorptions and Langmure‐type surface reactions under the relationship between oxygen activity ( a O ) and the electrode potential. To determine the reaction constant ( ka ) and four adsorption equilibrium constants at TPB ( K H, K H2O, K O and K OH ), a mashine learning approach with a genetic algorithm as an optimization method and the experimental data of reversible SOFC/ECs with different H2 /H2 O partial pressures as the learning data was developed. As a result, even though all experimental curves of the current density vs. a O in SOFC operation were fitted by numerous sets of the five constants, the coverages under different conditions could be uniquely determined. Results suggest that TPB at 900 °C was almost vacant with a small amount of H2 O in SOEC operation, and was not vacant and the OH coverage increased with increasing a O in SOFC operation.